An Analysis of Foreign Direct Investment in India: Understanding the Impact and Trends of Foreign Direct Investment in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Apart from being a critical driver of economic growth, foreign direct investment (FDI) is a major source of non-debt financial resource for the economic development of India. Foreign companies invest in India to take advantage of relatively lower wages, special investment privileges such as tax exemptions, etc. For a country where foreign investments are being made, it also means achieving technical know-how and generating employment.Foreign direct investment (FDI) plays a multidimensional role in the overall development of the host economies, which acts as a major catalyst in the development of a country through up-gradation of technology, managerial skills and capabilities in various sectors. It plays a complementary role in overall capital formation and in filling the gap between domestic savings and investment. At the macro-level, FDI is a non-debt-creating source of additional external finances. At the micro-level, FDI is expected to boost output, technology, skill levels, employment, and linkages with other sectors and regions of the host economy. The present study is an attempt to provide a detailed understanding of the spatial and sectoral spread of FDI-enabled production facilities in India and their linkages with the development of Indian economy. In this paper, we will review the current literature related to FDI, and use of secondary data to employ Karl Pearson’s correlation and regression (OLS Model) to estimate the trends of FDI in India. The study found that FDI affects the Gross domestic product (.683), Foreign Exchange Reserve (.717) Sensex(.618) and Nifty(.618) positive and highly correlated, while the impact of FDI on Gross capital Formation(.375) and Gross Domestic saving(.025) Was very low and insignificant